The Use of Revision Version of Archiving Interactive Digital Book Based on the Curriculum 2013 in Vocational School - Patni Ninghardjanti; C. Dyah Sulistyaningrum Indrawati; Andre N. Rahmanto; Chairul Huda Atma Dirgatama (Intelektual Pustaka Media Utama, 2018)
Information and communication technology has a large potency to help teachers and students to in a successful learning. The implementation of revision version of curriculum 2013 based digital book in school should include need analysis, preparing the necessary need, designing learning model and its development. The use of revision version of the curriculum 2013 based digital book is a decision made by teachers based on learning design. Considering a survey conducted, it can be found that there has be no archiving book corresponding to the revision version of 2013 curriculum. The use of revision version of curriculum 2013 based digital book is expected to improve the students’ learning interest and to optimize the teachers’ role as learning designer and mediator.